-4x - 3y= -7
6x+2y= -17
3y = -4x +7
y= -4x/3 + 7/3
substitute into the second eq.
6x + 2(-4x/3 + 7/3) = -17
6x -8x/3 + 14/3 =-17
10x/3 = -17 -14/3 = -65/3
x= (-65/3) ( 3/10)
x= -65 / 10 = -13/2
y= 4(13)/6 +7/3 = 11.
2006-12-18 08:27:39
·
answer #1
·
answered by Anonymous
·
3⤊
0⤋
-4x - 3y= -7
6x+2y= -17
=> 3y = -4x +7
y= -4x/3 + 7/3
substitute into the second equation:
6x + 2(-4x/3 + 7/3) = -17
6x -8x/3 + 14/3 =-17
10x/3 = -17 -14/3 = -65/3
x= (-65/3) ( 3/10)
x= -65 / 10 = -13/2
back into the first:
y= 4(13)/6 +7/3 = 11.
so x=-13/2 and y=11
2006-12-19 17:51:20
·
answer #2
·
answered by lobis3 5
·
2⤊
0⤋
-4x - 3y= -7
6x+2y= -17
=> 3y = -4x +7
y= -4x/3 + 7/3
6x + 2(-4x/3 + 7/3) = -17
6x -8x/3 + 14/3 =-17
10x/3 = -17 -14/3 = -65/3
x= (-65/3) ( 3/10)
x= -65 / 10 = -13/2
y= 4(13)/6 +7/3 = 11.
so x=-13/2 and y=11
:D
2006-12-20 11:05:47
·
answer #3
·
answered by pedazodegente 1
·
1⤊
0⤋
-4x - 3y = -7
6x + 2y =17
add the like numbers of both equations together
2x - y = 10
now multiply this new equation by 2and add it to the 2nd original equation
4x - 2y = 20
6x +2y = 17
10x =17 so divide both sides and x = 1.7
2006-12-18 16:35:11
·
answer #4
·
answered by Grev 4
·
0⤊
0⤋
solve for x then solve for y.
ie
-3y= -7+4x
y = 7/3 -4/3 x
plug that into the second equation to find x.
2006-12-18 16:25:48
·
answer #5
·
answered by K-chan 2
·
0⤊
1⤋
-4x-3y=-7 6x+2y=-17
-4x=-7+3y 6(-7/4+-3/4y)+2y=-17
x=-7/4+-3/4y -21/2+-18/4y+2y=-17
-21/2+-10/4y=-17
-10/4y=-6 1/2
y=130/8
y=65/4
-4x-3y=-7
-4x-3(65/4)=-7
-4x-195/4=-7
-4x=167/4
x=-167/16 (167/16, 65/4)
Should be your answer, I may have made a mistake though...
2006-12-18 16:33:34
·
answer #6
·
answered by locomonohijo 4
·
0⤊
0⤋
-4x - 3y= -7: in this problem u must subtract the two numbers in front of the equal sign because the operation is subtraction. so negative 4 minus 3 is negative 7, which u bring to da other side to negative 7. divide. negative 7 divide by negative 7 is equal to 1.
sorry i dont get the second one.
2006-12-18 16:33:35
·
answer #7
·
answered by dementor012 3
·
0⤊
1⤋
-4x - 3y= -7
6x+2y= -17
-12x - 9y = -21 (1)
12x + 4y = -34 (2)
(1) + (2)
-5y = -55
y = 11
-4x - 3y= -7
-4x - 33= -7
-4x = -26
x = 6.5
x = 6.5, y = 11
2006-12-18 16:26:44
·
answer #8
·
answered by Tom :: Athier than Thou 6
·
1⤊
0⤋
-4x - 3y= -7 multiply by 2
-8x-6y=-14
6x+2y= -17 multiply by 3
18x+6y=-51
-8x-6y=-14 add
10x=-65 divide by 10
x=-6.5
-4x - 3y= -7 substitute
-4(-6.5)-3y=-7
26-3y=-7 subtract 26 from each side
-3y=-33 divide by -3
y=11
(-6.5, 11)
2006-12-18 16:28:27
·
answer #9
·
answered by yupchagee 7
·
1⤊
0⤋
( -4x - 3y = -7)*-2
(6x+2y= -17)*3
8x+6y=14
-18x+6y= -51
10x= -65
x= (-6.5)
-4(-6.5)-3y=-7
-3y=-33
y=11
answer: (-6.5, 11)
2006-12-18 16:42:00
·
answer #10
·
answered by firewrksgoboom 2
·
0⤊
0⤋